The Pedagogy of English Language Teaching using CBSE Methodologies for schools. - Hyder, Huma (Advances in Social Sciences Research Journal, 2021)
Progressive Globalization established the necessity of workforce to possess excellent communication skills in multiple languages. Areas such as tourism, trade, media, technology, science, and others use common languages. However, countries like China, South Korea, and so forth discussed the need to teach one foreign language at primary as well as secondary school level and hence developed education policies that focused on teaching English as a foreign language or second language. Some countries like Malaysia, Philippines, Singapore, and India already have English language as a second official language. Hence, English Language Education was considered as second foreign language which was accepted and now it is considered as a symbol of aspiring quality education in a national as well as international perspective. In 21st century, English is considered as an international link language which is been widely accepted by people across the world. Although, English language has a historical heritage of British Empire, it is best used to develop an individual’s cultural, technological, scientific and material needs that competes with the society. It is believed that language learning is not just acquiring the skills of listening, speaking, reading, and writing. Language learning is also about the language competence and the ways communicative competence has been applied in an integrated manner. English language learning is not just an educational issue, it also addresses the issues of the society, national development, and personal advancement. In the present scenario, English Language acquired an inclusive place in most of the societies, especially in India. As a result, English Medium Schools have gained immense popularity which responds to aspiration of the people. This paper tries to present the significance of English as a Second language. The main purpose of this paper is to explore the significant pedagogies or methodologies used in schools to teach English as English language plays a crucial role in the education sector.